2015
DOI: 10.1155/2015/757680
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Copy Number Variation Affecting Genes Involved in the Cell Cycle Pathway: Implications for Somatic Mosaicism

Abstract: Somatic genome variations (mosaicism) seem to represent a common mechanism for human intercellular/interindividual diversity in health and disease. However, origins and mechanisms of somatic mosaicism remain a matter of conjecture. Recently, it has been hypothesized that zygotic genomic variation naturally occurring in humans is likely to predispose to nonheritable genetic changes (aneuploidy) acquired during the lifetime through affecting cell cycle regulation, genome stability maintenance, and related pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 99 publications
0
15
0
Order By: Relevance
“…A link between CNVs and Somatic Copy Number Alterations/Aberrations (SCNAs), which are changes in copy number that have arisen in somatic tissue, has emerged from studies of Iourov and colleagues who examined the frequency of CNVs mapping to the cell cycle pathway within a cohort of patients with intellectual disability, autism, and/or epilepsy (Iourov et al, 2015). The rationale for this study was based on the knowledge that somatic mosaicism is likely the consequence of alterations in cell division and genome maintenance pathways (as described in Section 2).…”
Section: Gin-cin Complexity: a Two Sided Coinmentioning
confidence: 99%
“…A link between CNVs and Somatic Copy Number Alterations/Aberrations (SCNAs), which are changes in copy number that have arisen in somatic tissue, has emerged from studies of Iourov and colleagues who examined the frequency of CNVs mapping to the cell cycle pathway within a cohort of patients with intellectual disability, autism, and/or epilepsy (Iourov et al, 2015). The rationale for this study was based on the knowledge that somatic mosaicism is likely the consequence of alterations in cell division and genome maintenance pathways (as described in Section 2).…”
Section: Gin-cin Complexity: a Two Sided Coinmentioning
confidence: 99%
“…One should keep in mind that it is impossible to obtain brain samples from a living individual to monitor somatic genome variations for a long period. However, it is possible to correlate the results of behavioral studies with somatic mosaicism evaluations in mitotic tissues and assessment of brain tissue susceptibility to genome instability uncovered by whole-genome scanning technologies (as suggested in [ 28 , 68 ]). In addition, basic research of correlation between somatic mosaicism levels in mitotic and post-mitotic neuronal and non-neuronal (brain) tissues should be pursued.…”
Section: Discussionmentioning
confidence: 99%
“…CIN presenting as monosomy and trisomy has been confirmed in all of these cases. CIN cases have also exhibited 4-9 copy number variations (CNV) encompassing genes, involved in the pathways to genome instability and somatic mosaicism (genome stability, DNA reparation/replication, mitotic checkpoint, cell cycle regulation and programmed cell death) [35][36][37]. Using bioinformatics for processing molecular karyotypes and addressing previously published data [8,12,18,20,25,[38][39][40][41][42], we have concluded that a proportion of these cases of intellectual disability, autism, epilepsy and/or congenital malformations is likely to be associated with chromosomal instability, which is an element of the pathogenetic cascade and thereby, should be recognized as a contributor to the phenotypic manifestations.…”
Section: Original Experiencementioning
confidence: 99%
“…Molecular karyotyping should be performed with an extended bioinformatics analysis of functional consequences of genomic variations to unveil the impact on molecular pathways involved in maintaining genome stability. It is to note that such genomic variations are indirectly involved in the pathogenesis being, therefore, frequently overlooked [37,39]. Thus, cytogenetic and FISH-based analyses of CIN should be complemented by the aforementioned bioinformatics evaluations.…”
Section: An Algorithm For Uncovering Disease Mechanisms Mediated By Cinmentioning
confidence: 99%